Beckett's creatures: art of failure after the Holocaust - Anderton, Joseph (2013)
The Beckettian creature is a product of dehumanisation and endures a variety of irresolvable tensions which culminate in a contingent mode of being that subsists in the nostalgia or hope for an authentic, meaningful life. This thesis examines Samuel Beckett's evocation of the 'creature' as an ontological concept to make the case for the oblique historical and political significance of his artistic forms. My work traces the aesthetic, biopolitical and humanistic resonance of the creature to contribute new ways of analysing Beckett's 'art of failure' in the post-Holocaust context. Through close readings of Beckett's prose and drama, particularly texts from the middle period, including Mol/ay, Ma/one Dies, The Unnamab/e, Waiting/or Godot and Endgame, I explicate four arenas of creaturely life in Beckett. Each chapter attends to a particular theme - testimony, power, humour and survival- to analyse a range of pressures and impositions that precipitate the creaturely state of suspension. I draw on the philosophical and theoretical writings of Theodor Adomo, Giorgio Agamben, Waiter Benjamin and Jacques Derrida to relate Beckett's creatures to a framework of critical theory that addresses the human condition and the status of art in the second half of the twentieth century. The key findings of this thesis are that Beckett's creatures traverse the edge of a bare life devoid of meaning, but live on through the debased idea of the human as they negotiate pressing obligations and melancholic repetition compulsions. Beckett invents author-narrators and narrative modes replete with epistemological and expressive failures, which act as an appropriate aesthetic response and pertinent reflection of the destabilised human after the Holocaust. As such, Beckett conveys the anti-humanist vision that attends the perverse or ineffective performance of humanist assumptions.